The middle Cambrian Linyi Lagerstätte from the North China Craton: a new window on Cambrian evolutionary fauna. Issue 7 (5th April 2022) - Sun, Zhixin; Zhao, Fangchen; Zeng, Han; Luo, Cui; Van Iten, Heyo; Zhu, Maoyan
Abstract: The rapid appearance of major animal groups and complex marine communities during the Cambrian explosion is recorded in large part in Burgess Shale-type lagerstätten. However, the restricted temporal and spatial distribution of known lagerstätten continues to hinder the formation of a comprehensive perspective on Cambrian evolutionary faunas. Here we describe the Linyi Lagerstätte (ca. 504 mya), a new Cambrian Miaolingian lagerstätte from the Zhangxia Formation in Shandong Province, North China. The Linyi Lagerstätte contains a variety of well-preserved soft-bodied fossils, among which the non-trilobite arthropods, particularly the mollisoniids and radiodonts, are the most important groups. The new assemblage is remarkable for its excellent preservation of arthropod limbs, eyes and guts, as well as for its close similarity in taxonomic composition to Laurentian lagerstätten. The distinctive Linyi Lagerstätte holds great promise for providing additional insights into the morphological disparity, community structure and paleogeographic range of marine faunas during the middle Cambrian (Miaolingian). Abstract : The large tempo-spatial discrepancy of distribution of the soft-bodied fossil lagerstätten limits our understanding of the Cambrian explosion of animals on Earth. The discovery of the Linyin Lagerstätte (∼504 mya) in North China reported by Sun et al. provides a new window into this critical evolutionary event.